Mid-term mortality after stenting of distal left main stenosis with regular, third generation drug eluting stent or dedicated bifurcation stent or surgery-registry based, all-comers data. (14th October 2021) - Vassilev, D; Zlatancheva, G; Shumkova, M; Nikolov, P; Gil, R
Abstract: Background: Distal left main (LM) bifurcation lesions remain a challenge for interventional cardiologists and they are associated with significant morbidity and mortality. The aim of the current study was to identify predictors of cardiac mortality at mid-term follow up after PCI (DES vs. dedicated bifurcation stent) or CABG. Methods: All patients with distal LM stenosis ≥50% were included in prospective registry starting from 01.2015. The exclusion criteria for registry are cardiogenic shock, a priory life expectancy duration <1 year, lack of inform consent. All patients were prospectively followed about the alive status through the national security number data base. All deaths were deemed cardiac if proof otherwise (the data patient families or family's physicians were contacted through phone call about the reason of death) Results: For three year follow up period (median 35 months, IQR 18–50) 303 patients were included. 220 patients were stented with 3rd generation DES, 43 with dedicated bifurcation stent BiOSS (Balton, Poland), and rest were sent for CABG. The mean age was 67±10 years, 72% were males, 37% diabetics, all with hypertension, 97% dyslipidemia, 15% PAD, 9% COPD, 16% carotid artery disease, previous MI 28%, previous PCI 50% - without significant difference between three groups. The frequency of acute coronary syndrome during admission was 11% - without difference in frequency between groups. The patient referred to CABG had significantly lower left ventricular EDV and ESV, more severe mitral regurgitation and kinetic disturbances, higher SYNTAX score and longer lesion length. On univariate COX regression analysis, the following factors were associated with mortality: age, NYHA class, GFR, baseline troponin, hemoglobin, LV EF, mitral regurgitation, kinetics disturbances, treatment with beta blockers, ACE inhibitors, statin, atrial fibrillation, SYNTAX score, lesion length. The type of treatment was not associated with differences in mortality (figure). On COX multiple regression survival analysis independent predictors of survival were: age (HR=1.036, CI 1.005–1.068, p=0.023); COPD (HR=2.313, CI 1.170–4.572, p=0.016); GFR (HR=0.988, CI 0.978–1.000, p=0.048); hemoglobin (HR=0.970, CI 0.955–0.986, p=0.000); left ventricular EF (HR=0.958, CI 0.832–0.985, p=0.003). Conclusions: The type of treatment was not associated with mid-term mortality. Our data demonstrate that dedicated bifurcation stent could be used safely for distal LM stenosis treatment with similar safety as 3rd generation DES. FUNDunding Acknowledgement: Type of funding sources: None.